Human Resource Management in Improving the Quality of Graduates of Islamic Boarding School - Nurmadiah, Nurmadiah; Syukri, Ahmad; Firdaus, Abdullah (Journal of Social Work and Science Education, 2025)
This study aims to analyse teacher resource management in improving the quality of graduates of Islamic boarding schools in Riau Province. This study reveals that effective teacher management is a key factor in producing quality graduates. The results showed that the boarding school leaders have carried out various managerial strategies, such as improving teachers’ welfare, providing fair compensation, continuous professional development, creating a supportive work environment, and conducting regular performance evaluations. In addition, collaboration with the government, community institutions, and the private sector is also carried out to support optimal human resource management. The quality of graduates of Islamic boarding schools in Riau Province is characterized by a deep understanding of the Qur’an and Hadith, mastery of religious and general knowledge, and basic skills coupled with noble character. The dual curriculum approach that combines religious and general education, supported by a mastery learning-based learning system and periodic evaluation, has proven to be able to produce graduates who are not only academically proficient, but also have strong character and readiness to face global challenges. This finding emphasizes the important role of teacher resource management in creating a holistic and highly competitive boarding schools’ education.